Our experience with the anterior interosseous artery fasciocutaneous flap for local and distant soft tissue reconstructions. Issue 8 (August 2022) - Franchi, Alberto; Scaglioni, Mario F.; Fritsche, Elmar
Summary: Background: Martin and his colleagues in 1989 described for the first time a fasciocutaneous flap based on a posterior branch of the anterior interosseous artery (AIA). Despite its promising characteristics, this flap never achieved popularity and the literature about it is limited. The aim of the present study is to share our experience with the AIA flap both as a local and free flap in reconstructing defects of various body regions. Patients and Methods: A retrospective review of 26 consecutive patients operated between January2001 and August 2020 was conducted. Seventeen male and nine female patients, mean age 52 years, underwent reconstruction of local and distant soft tissue defects using the AIA flap. Fourteen flaps were raised as free flap and 12 as local flaps for a total of 26 flaps. The locations of the defects included the face, the lower limb, the hand dorsum, and fingers. Results: Twenty-four out of 26 flaps survived completely, and two pedicled flaps presented partial necrosis, with one requiring a new free flap procedure. One free anterior interosseous flap required revision of the venous anastomosis. Two donor site dehiscence were observed, and they both healed by secondary intention healing. Follow-ups were conducted for a mean of 18 months. All patients showed good contour restoration of the affected body part. Conclusions: The AIA flap, either free or pedicled, represents a reliable tool to perform "like-with-like" reconstructions of hand defects. In some occasions, it is well suited for shallow defects in other body parts.